FEMALE LABOR MIGRATION AND ITS CONTRIBUTION TO THE FAMILY ECONOMY - Sitti Nurtina (The Indonesian Islamic Studies and International Relations Association (Insiera), 2019)
International migration occurs due to population growth that is not matched by growth in opportunities and job availability. Increased labor force and limited domestic employment, making the flow of labor migration abroad increased. International migration as labor is dominated by female workers (TKW). The increasing flow of labor migration of Indonesian women in abroad, even beyond men, shows the importance of understanding what is behind their movement. Especially women who are already married must have a reason to immigrate. For rural and married women who do not have many skills, international migration is a golden opportunity to improve their family's economy. This research is qualitative by using method of textual study by analyzing secondary data from various related literatures, then completed by semi structured interview with some main respondents that former female worker. Empirical data shows that married women working overseas due to economic considerations. Initiatives for work generally come from women themselves, whereas family members only approve. Thus, women have more freedom and confidence to decide to work overseas